2015
DOI: 10.18632/oncotarget.5390
|View full text |Cite
|
Sign up to set email alerts
|

An mRNA expression signature for prognostication inde novoacute myeloid leukemia patients with normal karyotype

Abstract: Although clinical features, cytogenetics, and mutations are widely used to predict prognosis in patients with acute myeloid leukemia (AML), further refinement of risk stratification is necessary for optimal treatment, especially in cytogenetically normal (CN) patients. We sought to generate a simple gene expression signature as a predictor of clinical outcome through analyzing the mRNA arrays of 158 de novo CN AML patients. We compared the gene expression profiles of patients with poor response to induction ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 58 publications
0
55
0
Order By: Relevance
“…To further evaluate the potential of DOCK1 expression as a prognostic marker for AML, we compared the survival impact of DOCK1 expression with other published gene expression-based prognostic signatures. We performed pairwise multivariate Cox analysis of DOCK1 expression with each of the published 3-gene, [ 12 ] 7-gene, [ 13 ] 11-gene, [ 14 ] and 24-gene predictors [ 15 ]. Notably, DOCK1 expression remained a prognostic factor independent to all these composite signatures (with multivariate Cox p<0.05) and achieved even higher significance in most of the comparison settings (10 out of 12; Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate the potential of DOCK1 expression as a prognostic marker for AML, we compared the survival impact of DOCK1 expression with other published gene expression-based prognostic signatures. We performed pairwise multivariate Cox analysis of DOCK1 expression with each of the published 3-gene, [ 12 ] 7-gene, [ 13 ] 11-gene, [ 14 ] and 24-gene predictors [ 15 ]. Notably, DOCK1 expression remained a prognostic factor independent to all these composite signatures (with multivariate Cox p<0.05) and achieved even higher significance in most of the comparison settings (10 out of 12; Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of specific cytogenetic abnormalities, such as t(15;17), t (8;21) or inv(16)/t (16;16), predicts a favorable prognosis, whereas t(9;22), 11q23 abnormalities, -5/5q-, -7/7q-, or complex karyotypes have adverse impact on clinical outcome in de novo AML patients [4]. Unfortunately, although several cytogenetic factors have been widely incorporated into clinical consideration for choosing treatment regimens, approximately one-half of the patients are cytogenetically normal patients which are usually assigned to intermediate prognostic group [5,6]. Besides gene mutations (CEBPA, NPM1, C-KIT, FLT3, etc.…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant differences between the two groups in sex, race, FAB classification, chemotherapy, transplant, genetic mutations (NPM1, FLT3, IDH1, IDH2, RUNX1) (all P value > 0.05). The baseline characteristics patients in GSE12417 and GSE71014 had already described in previous studies (18,19). Kaplan-Meier survival curves suggested that CD52 high was an adverse factor for chemotherapy group (EFS, p = 0.041; OS, p = 0.013; Fig.…”
Section: Baseline Patient Characteristicsmentioning
confidence: 58%